2018
DOI: 10.1021/acs.biochem.8b00837
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Competition: Characterizing and Eliminating Competitive Binding at Separate Sites between DAHP Synthase’s Essential Metal Ion and the Inhibitor DAHP Oxime

Abstract: 3-Deoxy-D-arabinoheptulosonate 7-phosphate (DAHP) oxime is a transition state mimic inhibitor of bacterial DAHP synthase, with K i = 1.5 μM and a residence time of t R = 83 min. Unexpectedly, DAHP oxime inhibition is competitive with respect to the essential metal ion, Mn 2+ , even though the inhibitor and metal ion do not occupy the same physical space in the active site. This is problematic because DAHP synthase is activated by multiple divalent metal cations, some of which have significant intracellular con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…In cases of partial inhibition, i.e., residual activity at high inhibition concentrations, Eadie−Hofstee plots converge toward the y-axis at high substrate concentrations but become nonlinear at low substrate concentrations. 9 For both PEP and ManNAc, the Eadie− Hofstee plots were linear at high substrate concentrations and the lines converged toward the y-axis, supporting competitive inhibition with respect to both substrates. This was supported by the crystal structure, which showed NeuNAc oxime bound in the catalytic site (see below), meaning that inhibition is necessarily competitive with respect to both substrates.…”
Section: ■ Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…In cases of partial inhibition, i.e., residual activity at high inhibition concentrations, Eadie−Hofstee plots converge toward the y-axis at high substrate concentrations but become nonlinear at low substrate concentrations. 9 For both PEP and ManNAc, the Eadie− Hofstee plots were linear at high substrate concentrations and the lines converged toward the y-axis, supporting competitive inhibition with respect to both substrates. This was supported by the crystal structure, which showed NeuNAc oxime bound in the catalytic site (see below), meaning that inhibition is necessarily competitive with respect to both substrates.…”
Section: ■ Resultsmentioning
confidence: 78%
“…Eadie–Hofstee plots demonstrated that NeuNAc oxime’s mode of inhibition was competitive with respect to PEP and ManNAc (Figure ). In cases of partial inhibition, i.e., residual activity at high inhibition concentrations, Eadie–Hofstee plots converge toward the y -axis at high substrate concentrations but become nonlinear at low substrate concentrations . For both PEP and ManNAc, the Eadie–Hofstee plots were linear at high substrate concentrations and the lines converged toward the y -axis, supporting competitive inhibition with respect to both substrates.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations